The Effect of Seasonal and Annual Variation on the Quality of Polygonatum Cyrtonema Hua Rhizomes - Weiting Pu; Yefei Yu; Xiaoxiao Shi; Ye Shao; Bihuan Ye; Youwu Chen; Qiyan Song; Jianjun Shen; Haibo Li (Plants)
This study aims to reveal the interannual and seasonal variations in functional components in Polygonatum cyrtonema Hua. rhizomes and evaluate whether the variations significantly affect the quality of rhizomes as a traditional Chinese herbal medicine. The interannual and seasonal variations in total flavonoid content and total saponin content were analyzed. The global dynamic variation in secondary metabolites in the rhizomes during a five-year growth period and in two traditional harvesting seasons were investigated based on metabolomics method. Results clearly showed that the functional components in P. cyrtonema rhizomes exhibited a significant increase in accumulation during the one- to four-year growth period and a significant decrease in accumulation during the four- to five-year growth period. The most active accumulation occurred during the three- to four-year growth period. Drastic variations in functional components occurred from spring to autumn. The significant interannual variation and drastic seasonal variation were strongly associated with the enrichment in some pathways related to the biosynthesis of secondary metabolites and the metabolisms of amino acids. The interannual and seasonal variations in functional components significantly affected the quality of P. cyrtonema rhizomes. The four-year-old rhizomes had the most superior quality due to their higher content of functional components and much more newly formed components. The rhizomes harvested in spring or autumn had unequal quality because of their significant differences in composition and content of functional components. Specifically, the rhizomes from spring contained more flavonoids, alkaloids, and phenolic acids, while those from autumn comprised more steroids. In conclusion, this study reveals that the interannual and seasonal variations in functional components can significantly affect the quality of P. cyrtonema rhizomes as a traditional Chinese herbal medicine. This study provides foundational insights and theoretical guidance for determining an optimal cultivation period to obtain medicinal rhizomes with superior quality. It also offers a strategy for harvesting medicinal rhizomes in two different seasons to achieve unequal quality.